Definition of energy efficient law of mechanical impact in vibratory stress relief of metal parts - Sheremet, Oleksii; Ivchenkov, Mykola; Ivchenkova, Olena; Sheremet, Kateryna (Eastern-European Journal of Enterprise Technologies, 2019)
The study is based on the method of vibratory stress relief, which is used to reduce the residual stresses in cast and welded parts, and is an alternative to thermal deformation methods, because it is unpretentious to the mass, shape and dimensions of the part. Vibratory stress relief is usually carried out using unbalance electromechanical systems, which are simple in design of the power section and control system. In such systems, processing occurs simultaneously at only one resonant frequency. The workpiece, as a rule, is characterized by several resonant frequencies that have a tendency to shift to the low-frequency region during the implementation of the vibration effect. The technological process of sequential processing at each variable resonant frequency is rather time-consuming and not efficient in terms of the cost of electrical energy. In order to reduce the cost of time and energy, this study proposes the use of the most advanced processing methods at several resonant frequencies. Based on the algorithms of sequential vibratory stress relief at several resonant frequencies of the part and their changes towards low ones, it was proposed to carry out processing by a polyharmonic perturbing force in a limited frequency band. This effect has a bandwidth that contains all the possible frequencies of the part where vibratory stress relief occurs. Such an effect can be realized with the help of an electrodynamic linear motor as an executive body. The advantage of an electrodynamic linear motor is the proportionality of the generated force to the current supplied to the moving conductor and its repetition in form. By means of mathematical modeling for the selected example, it was found that narrowing the frequency range in the low-frequency region by 5 times reduces energy costs by more than 4,000 times as compared with the broadband law of mechanical action on a part. A theoretically determined energy-efficient law can be software-implemented in control systems for electrodynamic linear motors that implement vibratory stress relief